Radon transfer from thermal water to human organs in radon therapy: exhalation measurements and model simulations - Hofmann, W.; Winkler-Heil, R.; Lettner, H.; Hubmer, A.; Gaisberger, M. (Radiation and environmental biophysics, 2019)
The transfer of radon from thermal water via the skin to different human organs in radon therapy can experimentally be determined by measuring the radon activity concentration in the exhaled air. In this study, six volunteers were exposed to radon-rich thermal water in a bathtub, comprising eleven measurements. Exhaled activity concentrations were measured intermittently during the 20 min bathing and 20 min resting phases. Upon entering the bathtub, the radon activity concentration in the exhaled breath increased almost linearly with time, reaching its maximum value at the end of the exposure, and then decreased exponentially with time in the subsequent resting phase. Although for all individuals the time-dependence of exhaled radon activity was similar during bathing and resting, significant inter-subject variations could be observed, which may be attributed to individual respiratory parameters and body characteristics. The simulation of the transport of radon through the skin, its distribution among the organs, and the subsequent exhalation via the lungs were based on the biokinetic model of Leggett and co-workers, extended by a skin and a subcutaneous fat compartment. The coupled linear differential equations describing the radon activity concentrations in different organs as a function of time were solved numerically with the program package Mathcad. An agreement between model simulations and experimental results could only be achieved by expressing the skin permeability coefficient and the arterial blood flow rates as a function of the water temperature and the swelling of the skin.